Fragmentos de lo doméstico : hacia una re-figuración del sujeto femenino en la obra temprana de Karen Lamassonne (2017)
"The following work proposes, from a selection of works made by the artist Karen Lamassonne from 1976 to 1982 in Colombia, to rethink the relation between space and subject. More specifically, the way in which the artist as a woman is inscribed in her "habitual places": domestic, intimate and private spaces. The visual proposal of these works resounds in a political dimension because it generates in these contexts of the habitual and domestic, a reformulation of concepts conceived traditionally as opposites, such as identity and anonymity, private and public. The same case occurs with terms that have usually been seen as synonyms, such as common and the public, or intimate and the private. In this way, artistic practices allow reconfiguration and reconstruction of social imaginaries, proposing other figures and images - which may eventually be reappropriated - and new ways of conceiving the future, the present and the past." -- Tomado del Formato de Documento de Grado.